2015
DOI: 10.1016/j.wem.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Heat Pack–Based Method For Consistent Heating of Intravenous Fluids

Abstract: The IVF heating system described here reliably delivered physiologically appropriate temperature intravenous fluids in 2 of the 3 ambient treatment conditions. With the appropriate number of FRH for the ambient conditions, this system enables the delivery of warmed IVF to provide active warming, which may be clinically beneficial in the prevention and treatment of hypothermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…41 Comparisons of rewarming modalities have been traditionally run with mildly hypothermic healthy volunteers, and results are accepted as generalizable to more severe forms of hypothermia. 42,43 LIMITATIONS Intravenous fluids were delivered with neoprene pouch, flow rate, and environmental conditions identical to those tested and described in a prior study, 31 although the liter bag was warmed in circulating water rather than by flameless ration heaters. Because the internal temperature was identical, it is unlikely there was any difference in delivery temperature, although this was not directly measured in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…41 Comparisons of rewarming modalities have been traditionally run with mildly hypothermic healthy volunteers, and results are accepted as generalizable to more severe forms of hypothermia. 42,43 LIMITATIONS Intravenous fluids were delivered with neoprene pouch, flow rate, and environmental conditions identical to those tested and described in a prior study, 31 although the liter bag was warmed in circulating water rather than by flameless ration heaters. Because the internal temperature was identical, it is unlikely there was any difference in delivery temperature, although this was not directly measured in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous fluids were delivered with neoprene pouch, flow rate, and environmental conditions identical to those tested and described in a prior study, 31 although the liter bag was warmed in circulating water rather than by flameless ration heaters. Because the internal temperature was identical, it is unlikely there was any difference in delivery temperature, although this was not directly measured in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study examining the impact of infusing warmed (32°C) versus control (23.2°C) fluid during air‐ambulance transport found that patients who received warm fluid had a higher core temperature (36.8°C vs 35.5°C) on arrival to the emergency department 6 . The unavailability of devices designed for heating intravenous fluid in the field has led some EMS personnel to improvise methods using available resources 7 …”
Section: Introductionmentioning
confidence: 99%